2004
DOI: 10.1182/blood-2004-04-1333
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the chromatin structure and cis-element organization of the human and mouse GATA1 loci: implications for cis-element identification

Abstract: Cis-element identification is a prerequisite to understand transcriptional regulation of gene loci. From analysis of a limited number of conserved gene loci, sequence comparison has proved a robust and efficient way to locate ciselements. Human and mouse GATA1 genes encode a critical hematopoietic transcription factor conserved in expression and function. Proper control of GATA1 transcription is critical in regulating myeloid lineage specification and maturation. Here, we compared sequence and systematically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 72 publications
6
66
1
1
Order By: Relevance
“…9A). GATA-1 is able to stimulate its own GATA-1 promoter activity (33); the GATA-1-binding sites could be systematically mapped on the GATA-1 gene locus (37). We confirmed the described GATA recruitment to GATA-1 gene enhancer elements and found a clear correlation with the presence of Mediator subunits Med1 and Med17, as well as polII.…”
Section: Discussionsupporting
confidence: 70%
“…9A). GATA-1 is able to stimulate its own GATA-1 promoter activity (33); the GATA-1-binding sites could be systematically mapped on the GATA-1 gene locus (37). We confirmed the described GATA recruitment to GATA-1 gene enhancer elements and found a clear correlation with the presence of Mediator subunits Med1 and Med17, as well as polII.…”
Section: Discussionsupporting
confidence: 70%
“…Similar results have been published previously for definitive erythroid hematopoiesis (84). We observed that hyperacetylated histone H3 and H4 generally associated with open chromatin(85) at the previously identified DNase I hypersensitive sites in both definitive (fetal liver) and primitive (yolk sac) erythroid cells ( figure 4C).…”
Section: Regulation Of the Gata-1 Locus In Mast Cellssupporting
confidence: 79%
“…We observed that hyperacetylated histone H3 and H4 generally associated with open chromatin(85) at the previously identified DNase I hypersensitive sites in both definitive (fetal liver) and primitive (yolk sac) erythroid cells ( figure 4C). The DNase I hypersensitive sites represent erythroid and megakaryocyte enhancers of the GATA-1 locus (86)(87)(88)(89)). An unexpected result in one of the controls of our analysis, however, was the finding of hyperacetylated histone H3 and H4 chromatin in the GATA-1 large first intron in the M1 myeloid cell line (figure 4B).…”
Section: Regulation Of the Gata-1 Locus In Mast Cellsmentioning
confidence: 99%
“…This difference in expression patterns probably results from the mouse's trans-acting environment being different from the human's. For example, GATA1, an erythroid transcription factor that interacts with the LCR, resides at a locus with marked differences in chromatin structure in mice and humans (51). Moreover, cis-elements in the GATA1 locus show greater binding affinity for trans-factors in mouse than in human erythroid cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…For example, GATA1, an erythroid transcription factor that interacts with the LCR, resides at a locus with marked differences in chromatin structure in mice and humans (51). Moreover, cis-elements in the GATA1 locus show greater binding affinity for trans-factors in mouse than in human erythroid cells (51). If this pattern holds for embryonic erythroid cells as well, then the different trans-acting transcriptional environments that apparently exist in human and mouse may account for human ␥ 1 being a major embryonic gene in transgenic mice but only a minor embryonic gene in humans, where it is the major ␤-type globin fetal gene.…”
Section: Discussionmentioning
confidence: 99%